Gold, Silver and Platinum Nanoparticles: From New Synthetic Routes to Sensing, Catalysis and Bio-Applications - Fernández-Lodeiro, Adrián (2019)
Gold, Silver and Platinum metallic nanoparticles have emerged as powerful tools with a wide array of applications in different fields, such as biomedicine, catalysis, and environmental sciences. The modification of nanoparticles´ metal composition, size, and shape lead to totally different properties of the nanomaterial. This tunable versatility is responsible for the vast array of applications of nanomaterials that affects the way we live now and will in the future. The project of this PhD thesis was designed with the main objective of developing new green and sustainable Nano-synthetic methodologies to obtain new Nano-particles for biomedical, chemical and environmental applications. In Chapter two it is described the chemical synthesis of new gold and silver functionalised nanoparticles, engineered to achieve naked-eye detection of a toxic metal ion, namely mercury, in aqueous and non-aqueous liquids. Such achievements were published in the journal Chemistry Open of Wiley, and also highlighted as journal front cover (IF 2.938). In chapters three and four the synthesis of new platinum nanoparticles with spherical or dendritic shapes to be used as catalysts is described. In addition, the catalytic applications were assessed in the reduction of p-nitrophenol in aqueous media. Moreover, our system shows catechol-oxidase activity, which allows oxidation of amino acid L-3,4-dihydroxyphenylalanine, a drug to treat Parkinson disease. The results were published in the Scientific Reports (IF 4.122), and in the Nano Research (IF 7.994), from Springer Nature editorial. In chapter five a new methodology for the preparation of gold nanorods covered with a mesoporous silica shell is described. The new systems were conjugated with doxorubicin and methylene blue and studied as new drug nanocarriers. Properties were successfully tested against Human Breast Adenocarcinoma (MCF7) cells and Gram-negative and Gram-positive bacteria as new antibiotics to fight microbial resistance. Results are presented in a manuscript under revision.